Arthroscopic Saucerization and Repair of the Lateral Discoid Meniscus - Law, Gin Way; Lee, Dave; Gupta, Shobhit; James HP Hui (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Surgical treatment of the symptomatic discoid lateral meniscus has undergone a paradigm shift since recognition of the development of accelerated osteoarthritis with subtotal meniscectomies. Current strategies have shifted towards meniscus preservation, and meniscoplasty is considered the gold standard of treatment at present. Meniscoplasty with saucerization of the meniscus recreates the standard crescent shape for improved shock absorption, load transmission and joint stability. This has shown good mid- to long-term outcomes in children and adolescents in the literature. As the discoid lateral meniscus is also associated with intrasubstance degeneration and meniscus tears, concomitant meniscus repair should be performed in line with efforts for meniscus preservation. In this technique manuscript, we detail our saucerization technique, considerations for meniscus repair, and tips to achieve a successful outcome.